PERAN ADVOKAT DALAM PRAPERADILAN (ANALISIS PUTUSAN PENGADILAN NEGERI SLEMAN NO.02/PID.PRA/2014/PN.SLMN) - , MUHAMMAD RIDWAN S ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Pre-trial is an institution which it aims to supervise horizontally against the law enforcement action of arbitrary. Pretrial is a positive action of law by upholding the law of an accused to an action which has a contrary to the law. Pretrial represents the ideals of positive law by upholding the rights of a suspect of an action he/she got as opposed to the law. In the Book of the Law of Criminal Procedure, a pretrial regulated in Article 1 point 10, Article 77 through Article 83. Besides, it regulates the compensation and rehabilitation, namely Article 95 through Article 97 that in this case the rights of the suspect to ask for damages and cleanup the reputation regarding actions taken arbitrarily by the investigator or prosecutor to himself about the arrest or detention. A lawyer has an important role in the pre-trial capacity as legal representative of the applicant. According to Act No. 18 of 2003 regarding the Advocate Act state that the advocate as a person who has a profession of giving legal services, both inside and outside the court which it meets the requirements under the provisions of this law. Legal services are the services provided by a lawyer which giving a legal consultation and support/aid, running the power, being represent, assisting, defending, and performing other legal action for the interest of the client or legal person, entity, or other institutions that receive the legal services from the advocate. Advocate is one of the pillars of law enforcement in Indonesia besides Judges, Prosecutors and Polices. By the knowledge of a legal advocate is be able to play a role in the law enforcement process in order to create the law itself which has the purpose of legal certainty, expediency and justice.